The didactic use of fossils as a teaching tool in Earth Sciences education - Calonge García, Amelia; Bercial, M.T.; García Sánchez, J.; López Carrillo, Mª Dolores (Pulso. Revista de educación, 2003)
Our proposal aims to familiarise students with the field of Palaeontology by engaging them in simple activities that dispel any preconceived notions they may hold and introduce them to basic paleontological concepts. The methodology and resources required for these activities can be assembled by the teacher from a variety of documentary sources on the subject, tailored to the students’ age group.